2018
DOI: 10.1177/1945892418770260
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Clinical Outcomes of Aspirin Desensitization With Continuous Daily Aspirin Therapy in Aspirin-exacerbated Respiratory Disease

Abstract: Background Aspirin-exacerbated respiratory disease (AERD), also known as Samter's triad or aspirin (ASA)-intolerant asthma, affects 7% of asthmatics and has a higher prevalence in those with chronic rhinosinusitis and concomitant nasal polyposis. ASA desensitization with daily ASA therapy is a uniquely beneficial treatment for this disease entity and has been shown to have a significant impact on symptom scores, polyp disease, and need for systemic corticosteroids. However, no long-term studies have demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
71
1
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 17 publications
4
71
1
4
Order By: Relevance
“…It is also important to note that the follow‐up period in the cardiovascular literature ranges from 3 to 10 years with much larger patient populations . In AERD literature, although observational studies with variable follow‐up periods up to 8 years have not demonstrated significant bleeding risk as portrayed in cardiovascular literature, they demonstrate a high discontinuation rate up to 38% due to side effects such as gastritis and easy bruising . Considering that aspirin desensitization in AERD involves a significantly higher daily dose of aspirin (650 to 1300 mg daily) than what is typically used for cardiovascular protection, the benefits of aspirin desensitization should be closely weighed against the potentially significant adverse effects, GI side effects, and hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that the follow‐up period in the cardiovascular literature ranges from 3 to 10 years with much larger patient populations . In AERD literature, although observational studies with variable follow‐up periods up to 8 years have not demonstrated significant bleeding risk as portrayed in cardiovascular literature, they demonstrate a high discontinuation rate up to 38% due to side effects such as gastritis and easy bruising . Considering that aspirin desensitization in AERD involves a significantly higher daily dose of aspirin (650 to 1300 mg daily) than what is typically used for cardiovascular protection, the benefits of aspirin desensitization should be closely weighed against the potentially significant adverse effects, GI side effects, and hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin desensitization and daily maintenance therapy benefits many patients with AERD. 3,7 Aspirin therapy has been shown to impart a long-term benefit of polyp regrowth reduction, improved sense of smell, and need for revision sinus surgery in prospective clinical trials. 6,[18][19][20] In addition to aspirin therapy, ESS has been shown to improve the disease process in both physician-reported (nasal endoscopy and Lund-Mackay [LM] computed tomography scores) and patient-reported (SNOT-22 score) measures.…”
Section: Discussionmentioning
confidence: 99%
“…6 Aspirin desensitization followed by daily maintenance appears to be safe and effective in improving airway disease and quality of life even after 10 or more years of continuous use. 7 Although ESS enhances aspirin treatment response in patients with AERD when performed 3-6 weeks before initiation of aspirin desensitization and treatment, 8 there is insufficient research on aspirin desensitization outcomes with and without antecedent ESS. In addition, aspirin seems to benefit some patients, even if surgery timing was not accounted for or if ESS was performed >12 months before start of aspirin treatment.…”
mentioning
confidence: 99%
“…Fish oil, the main source of omega‐3 polyunsaturated fatty acid, includes eicosapentaenoic acid and docosahexaenoic acid, which have been shown to have anti‐inflammation and protective actions in cardiovascular disease, rheumatoid arthritis, cystic fibrosis, and periodontitis . Treatment with omega‐3 fatty acid has been shown to significantly decrease osteoclast levels and osteoclastic activity related to bone resorption in rats …”
Section: Introductionmentioning
confidence: 99%
“…12,13 Treatment with omega-3 fatty acid has been shown to significantly decrease osteoclast levels and osteoclastic activity related to bone resorption in rats. 14,15 So far, many different drug classes have been found to be host-modulation agents, including non-steroidal antiinflammation drugs (NSAIDs). 16 NSAIDs are one of the most useful drugs in dentistry because they can stimulate the alveolar bone formation, or prevent the progression of alveolar bone loss in periodontitis.…”
Section: Introductionmentioning
confidence: 99%